Kualitas Pelayanan Kantor Pertanahan Kota Pekanbaru: Studi Pelayanan Alih Wilayah Sertifikat Tanah Pasca Pemekaran Kecamatan Tampan - Muhammad Kurnia Ramadhan; Harapan Tua Ricky Fredy Simanjuntak; Adianto Adianto (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This research was motivated by the efforts of the Pekanbaru City Land Office in serving Land Certificates that moved areas after the expansion of the Tampan District. Improving the service quality of the Pekanbaru City Land Office is a very important aspect in supporting land certificate area transfer services. The purpose of this research is to find out what are the obstacles faced by the Pekanbaru City Land Office in carrying out its duties in transferring land certificate areas after the division of Tampan District. The method used is qualitative research by conducting observations and in-depth interviews. This research determines research informants as a source of information to obtain the required data. The results of this study indicate that the service quality of the Pekanbaru City Land Office is still not optimal, this can be seen from the 6 main focus concepts of Service Quality according to Lijan Poltak Sinambela namely, Transparency, Accountability, Conditional, Participative, Equal Rights, Balance of Rights and Obligations. There are still a number of obstacles that must be resolved, namely, unclear service time processes, lack of employee response in terms of quality and speed of service, lack of service personnel in completing their duties for the process of transferring land certificates after the division of Tampan District